Maturação de frutos e sementes de Sideroxylon obtusifolium [(Roem.& Schukt.)T. D.Penn.] em diferentes safras. - Sena, Daniela Vieira dos Anjos (2016)
Quixabeira [Sideroxylon obtusifolium (Roem. & Schult.) T.D. Penn.] is a fruit of the Sapotaceae family, typical from the Caatinga that can be used in alternative medicine, animal feed and wood extraction. The study of seed maturation is an important way to have knowledge about the behavior of the species in relation to their reproduction, making possible to determine the appropriate time for harvesting in order to obtain good genetic materials, seeds suitable for the conservation and production of seedlings. To what has been exposed the aim of this study was to assess the maturation of fruits and seeds of S. obtusifolium in order to determine the point of physiological maturity. The research was conducted with 30 mother trees located at the Santa Rosa do Espólio farm, in the rural area of the town of Boa Vista - PB, in the Laboratories of Seed Analysis and Biology and Technology of Post-Harvest of the Center of agricultural sciences of the Federal University of Paraíba, Areia - PB. The determinations were: physical characteristics, water content of fruits and seeds, dry mass of seeds, germination test, first count and germination speed index, dry seedling length and mass, electrical conductivity and chemical composition of fruits and seeds (Soluble solids, content of starch, reducing sugars, lipids and total proteins). The statistical design used was entirely at random and the data submitted to the analysis of variance and polynomial regression, as a function of harvest times. During the development of fruits and seeds, there was a gradual increasing on fruit diameter, dry mass of seeds, germination, first count and germination speed index, seedling dry weight and length, soluble solids, content of starch, soluble sugars, total proteins. Also there were a reduction on water content and in the values of electrical conductivity in the seeds during maturation. The physiological maturity point for S. obtusifolium seeds occurs between 105 and 112 days after anthesis in the environmental conditions of Boa Vista-PB, and during the ripening of the fruits occurs accumulation of soluble solids and reducing sugars in fruits and seeds.